2020
DOI: 10.1186/s12872-020-01390-8
|View full text |Cite
|
Sign up to set email alerts
|

Impaired fasting glucose and major adverse cardiovascular events by hypertension and dyslipidemia status: the Golestan cohort study

Abstract: Background: Whether pre-diabetes in the absence of hypertension (HTN) or dyslipidemia (DLP) is a risk factor for occurrence of major adverse cardiovascular events (MACE) is not fully established. We investigated the effect of impaired fasting glucose (IFG) alone and in combination with HTN, DLP or both on subsequent occurrence of MACE as well as individual MACE components. Methods: This longitudinal population-based study included 11,374 inhabitants of Northeastern Iran. The participants were free of any cardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 39 publications
(37 reference statements)
2
7
0
Order By: Relevance
“…Although there have been few studies of the relationship of IFG in combination with borderline high LDL-C and CVD, a similar approach has been used to analyze the relationship of a combination of IFG and dyslipidemia with CVD. Hashemi et al (37) found that the risk of CVD was 1.30-fold higher in individuals with both IFG and dyslipidemia than in those with normal FBG and lipids, which is consistent with the present findings. In addition, we found that the risk associated with a borderline high LDL-C status increased, which may be related to the pathogenesis of atherosclerosis (38,39).…”
Section: Discussionsupporting
confidence: 93%
“…Although there have been few studies of the relationship of IFG in combination with borderline high LDL-C and CVD, a similar approach has been used to analyze the relationship of a combination of IFG and dyslipidemia with CVD. Hashemi et al (37) found that the risk of CVD was 1.30-fold higher in individuals with both IFG and dyslipidemia than in those with normal FBG and lipids, which is consistent with the present findings. In addition, we found that the risk associated with a borderline high LDL-C status increased, which may be related to the pathogenesis of atherosclerosis (38,39).…”
Section: Discussionsupporting
confidence: 93%
“…The results of this study found that people with diabetes or dyslipidemia are at higher risk for hypertension,and that both overweight and obesity are risk factors for hypertension.This is similar to the ndings of the Zhang FL's study,which found that individuals who are overweight/obese,have dyslipidemia or diabetes had a higher risk of developing hypertension [23] .Hashemi Madani N found that hypertension,dyslipidemia,and impaired fasting blood glucose were all likely to lead to an increase in adverse cardiovascular events [24] .de Lombera Romero F found that hypertension was often associated with other atherosclerosis risk factors,such as dyslipidemia,insulin resistance and obesity [25] .What's more, Hu L found that in South China, the increase of age and BMI were the risk factors for hypertension [26] .In addition,the present study veri ed the additive interaction between dyslipidemia and overweight or obesity.Jian S's studies showed that triglyceride index and obesity had an interactive effect on the incidence of hypertension in middle-aged and elderly people,and dyslipidemia and obesity were both risk factors for hypertension [27] .Related studies have shown that dyslipidemia and overweight/obesity have several common mechanisms for increasing blood pressure,for example,dyslipidemia can impair arterial endothelial function,leading to hypertension [28] .Previous studies have proved that obesity and the cardiovascular disease family have an interactive effect on hypertension [29] .There is an interaction between dyslipidemia and oral contraceptives that can increase the risk of high blood pressure [30] .However,few studies have explored whether there is interaction between dyslipidemia and overweight/obesity on hypertension.Therefore,based on the ndings in this study that overweight/obesity and dyslipidemia have interaction on hypertension,further studies on the interaction mechanism between these factors are needed in the future.…”
Section: Discussionsupporting
confidence: 82%
“…This is similar to the findings of Zhang FL’s study, which found that individuals who were overweight/obese and had dyslipidemia or diabetes had a higher risk of developing hypertension 22 . Hashemi Madani N found that hypertension, dyslipidemia, and impaired fasting blood glucose were all likely to lead to an increase in adverse cardiovascular events 23 . de Lombera Romero F found that hypertension was often associated with other atherosclerosis risk factors, such as dyslipidemia, insulin resistance and obesity 24 .…”
Section: Discussionmentioning
confidence: 99%